Restriction of Saraswati and Banyu Pinaruh Celebration during COVID-19 Pandemic in Bali - Rizky Januar (Bali Tourism Board, 2021)
Saraswati Day is a day to commemorate the descent of knowledge as a source of human intelligence. According to the Balinese calendar, Balinese people celebrate the day on Saniscara (Saturday) Wuku Watugunung, which falls every 210 days of the Balinese calendar or every six months according to the solar calendar. The high potential of public enthusiasm to commemorate Saraswati and Banyu Pinaruh days cannot be separated from the previous celebrations, which were always held in festive. Before the COVID-19 pandemic, these two days were crowded with activities from students and educators on Saraswati Day, then continued with the melukat ritual by the Balinese Hindu community at various water sources and holy places the next day in Banyu Pinaruh. The drastic shift in situation, If it is interpreted according to the purpose of Saraswati’s day itself, namely to gain wisdom, as the essence of knowledge, then the pandemic situation can be viewed as a new challenge in humankind. From the COVID-19 pandemic, humans are expected to be adaptive to their environment for the sake of mutual prosperity. Therefore, the obtained knowledge about everything that exists in this world would give a significant meaning. It would not be only a knowledge written in a book, learned, and stays on people’s heads. Nevertheless, it has become an applied science that is practiced and provides significant benefits for humankind.